Vivências dos fisioterapeutas egressos da Residência Multiprofissional em Saúde da Família e Comunidade - Costa, Mariana Lisboa (Universidade Federal de São Carlos, 2013)
A formation in health, seeking population real needs, requires that Higher Education Institutions (IES) and the Sistema Único de Saúde (SUS) observe commitment, cooperation and responsible relationships towards the professional development. The Multi-professional Residency Program in Health is configured as a potential strategy to the professional development of abilities and formation for SUS. In this context, the goal of the present study was to analyze the physiotherapists‟ experiences that attended a multi-professional residency program in family and community health- RMSFC at a public university, intending to verify the repercussions of the professional practice. In the current qualitative case study participated nine former physiotherapists from a RMSFC. In order to collect data it was employed an Oral Story technique. For so much, a trigger question was elaborated, intending to explore the historical path of the physiotherapists‟ practice. Therefore, the interviews had been transcripted and transcreated for the accomplishment of the analysis, in which the sense interpretation method had been used. In the analysis, it had been defined the following outstanding themes: 1) From different starting points- in a search for an identity, and coming from different starting points, they were Setting sail on unknown seas . 2) A meeting point where a new identity is built - the residency was considered as a meeting place where it is possible to build a new identity. 3) The awkwardness of the labor world: new challenges and perspectives - the physiotherapists revealed through their professional experiences life as it is and 4) The future to God belongs! - the subjects wish to pursue different paths pointing that the essence of the dream is the fulfillment of the desire . It has been observed that the residency had an important role in the professional formation of the former physiotherapists, mostly in regard to the acquisition of a broad vision in health care in the primary attention, in the interaction and teamwork with other professionals. Nevertheless, the residency cannot become the savior of the fragmented educational process of graduation. It is necessary to continue investing in this health formation, as well in changes concerning the professional profile according to the Curriculum National Guidelines. For the residency programs is suitable to inquire if the developments of abilities to deal with life like it is should not be part of the egresses profile.
Experiences of physiotherapists who graduated from residency in multiprofessional family health and community
Keywords: Residência multiprofissional em saúde; Atenção primária à saúde; Fisioterapia; Saúde da família; Formação de Recursos Humanos; Primary health care; Physiotherapy; Human resources formation; Family health; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL